Validation of the Short-Facebook Jealousy Scale among Colombian Men and Women - María del Mar Sánchez-Fuentes (Acta Colombiana de Psicología, 2023)
Social networks, particularly Facebook, influence romantic relationships, as they can generate jealousy and conflict between members of the couple. The Facebook Jealousy Scale (FJS) is an instrument that assesses jealousy about using Facebook, but no similar instrument is available in Colombia. The main aim was to examine the psychometric properties of the FJS in a Colombian sample of 485 men and 727 women. Participants answered the socio-demographic questionnaire, the adaptation of the Facebook Jealousy Scale, Romantic Partner Conflict Scale, Rosenberg Self-Esteem Scale and Romantic Jealousy Scale. The final version of the FJS was made up of 15 items which were distributed across three dimensions: Partner's Activity, Partner's Surveillance, Partner's Romantic and Sexual relationship. Ordinal's alpha values from its three factors ranged between .90 and .95. Concurrent validity was also provided, as the measure was associated with dimensions from partner conflict, self-esteem, and romantic jealousy. An invariance test by gender was also performed, resulting in compliance with metric invariance. Therefore, the FJS is a useful tool for clinicians and researchers who work on issues related to romantic relationships. Research analyzing Facebook jealousy provides an interesting indicator of couple's monitoring and controlling behaviors, which are features of psychological abuse, a subtype of intimate partner violence.